METHODOLOGICAL APPROACHES TO THE RESEARCH OF PSYCHOLOGICAL WELL-BEING OF RUSSIAN AND ARMENIAN STUDENTS - Samokhvalova, A.G.; Asriyan, E.V. (Modern Psychology, 2021)
The article raises the actual problem of studying the psychological well-being of students. The author's understanding of the "well-being", "psychological well- being" and "subjective well-being" of a person is presented. Psychological well-being is defined as an integral characteristic of the subject's states that ensure the consistency of all mental functions and processes, the achievement of internal balance and subjective integrity. Methodological approaches to the organization of a cross-cultural study of the psychological well-being of students enrolled in Russian and Armenian universities have been substantiated. As the most important approaches, the sociocultural approach is defined, which considers the development of a student in the context of his interaction with the environment, involving the study of the impact on the level of psychological well-being of the immediate social environment (especially the educational environment, family climate, social capital), and other macro-factors (ethnicity, national traditions, ideology, values, socio- economic way of life); as well as a contextual approach that allows us to consider the situation of full-time education at a university as a predictor of the psychological well-being of Russian and Armenian students, taking into account other contexts of  life (living with a family or apart from parents, living in a hometown or moving to another city, the "academic" option learning or combining study with work).